The Purification Method Using Iodixanol (Optiprep)-Based Density Gradient Significantly Reduces Cytokine/Chemokine Production from Human Islet Preparations, Leading to Prolong β-Cell Survival During Culture - Mita, Atsuyoshi (2009)
Improved islet isolation has still been important to obtain adequate islet numbers for islet transplantation. Although Ficol-based density gradient is widely used for purification in most islet processing centers, OptiPrep-based density gradient is recently used in the limited centers and their clinical outcomes are excellent. Cytokine/chemokine production from islet preparations for transplantation widely varies. Some cytokines/chemokines have been reported to cause apoptosis in human islet preparations after isolation. Reducing cytokine/chemokine production is a key to improve islet numbers after isolation and islet transplantation outcome. The aim of current study is to investigate the variability of pro-inflammatory cytokine/chemokine production from islet preparations purified by different density gradient. After digestion of human pancreata, pre-purification digests were devided into two groups and purified using semi-automated cell processor with Ficoll-based and OptiPrep-based density gradient. Islet preparations were cultured for 2 days and assessed regarding islet cell viability (FDA/PI), fractional β-cell viability and β-cell content. Cytokine/chemokine production from islet preparations was also examined. After purification, purity, post-purification IEQ and islet recovery rate were comparable between two groups. Although FDA/PI and fractional β-cell viability showed no significant differences, β-cell survival during culture significantly increased in OptiPrep-based density gradient group when compared to Ficoll-based density gradient group. TNF-α, IL-1β, IFN-γ, IL-6 and MIP-1β production from OptiPrep-based density gradient group significantly decreased. OptiPrep-based density gradient can reduce cytokine-production when compared to Ficoll-based density gradient, resulting in improvement of quantity of β-cell mass. Cytokine profiling could spot new light on assessment of islet preparations before transplantation.